2022
DOI: 10.1021/acs.jafc.1c07198
|View full text |Cite
|
Sign up to set email alerts
|

Technological and Biotechnological Processes To Enhance the Bioavailability of Dietary (Poly)phenols in Humans

Abstract: The health effects of (poly)phenols (PPs) depend upon their bioavailability that, in general, is very low and shows a high interindividual variability. The low bioavailability of PPs is mainly attributed to their low absorption in the upper gastrointestinal tract as a result of their low water solubility, their presence in foods as polymers or in glycosylated forms, and their tight bond to food matrices. Although many studies have investigated how technological and biotechnological processes affect the phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 117 publications
0
25
0
Order By: Relevance
“…On the contrary, in some studies, traditional thermal treatments have been reported to reduce the bioaccessibility of bioactives. For example, Rodríguez-Roque et al [11] reported the bioaccessibility of vitamin C, total phenolic acids and total flavonoids in fruit juice blends as 11.1, 17.2 and 15.5%, respectively, which were statistically lower than those of HPP-and high-intensity-PEF-treated samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in some studies, traditional thermal treatments have been reported to reduce the bioaccessibility of bioactives. For example, Rodríguez-Roque et al [11] reported the bioaccessibility of vitamin C, total phenolic acids and total flavonoids in fruit juice blends as 11.1, 17.2 and 15.5%, respectively, which were statistically lower than those of HPP-and high-intensity-PEF-treated samples.…”
Section: Introductionmentioning
confidence: 99%
“…Technological treatments may trigger chemical or physical modifications in foods, with a positive impact on the bioaccessibility and thus bioavailability of phenolics. These alterations include the release of phenolic substances from the matrix due to changes in food structure, as well as the protection of phenolic compounds throughout the gastrointestinal tract due to interactions between different food components [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have developed great interest in dietary polyphenols due to their association with health issues and the links affecting them. Large in vitro and in vivo studies have revealed the low bioavailability of polyphenols, along with their beneficial effects [ 20 ]. Allicin, present in garlic, whose bioavailability and bioequivalence were found to be unknown, was studied in 13 different subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are a category of secondary plant metabolites that incorporates a large number and variety of compounds ( Table 1 ) [ 6 , 7 , 8 ]. Such a variety of compounds incorporates a great variety of possible benefits, being able to find several beneficial effects for the same subclass and common effects in different classes and subclasses [ 9 , 10 , 11 ]. Of all the polyphenols studied as nutraceuticals or functional ingredients, we can highlight those that are better known as curcuminoids, betalains, and stilbenes, such as resveratrol, quinones as ubiquinol, and various flavonoids very studied, such as luteolin, genistein, hesperetin, quercetin, catechinsm and anthocyanidins ( Table 1 ) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%